(3OQGSGJ GdLOhi GdJLGQjI hGdEbJUGOjI h GdGLJeGYjI eY eTQhYGJ (BBOT /s - (3YWjI, YHO GdbGOQ eMeO YHO GdbGOQs ((3GdGScfOQjI(B: s (3GdOGQ GdLGeYjI(B, s, 2000)
(3OQGSGJ GdLOhi GdJLGQjI ddeTQhY(B:(3GdJYQja HOQGSGJ GdLOhi,OQGSI GdShb,GdJMdjd GdLOj debGQfI GdeTQhYGJ eGfYI GdJHGOd,GdLOhi GdJLGQjI, Jbhje GdeTQhYGJGdeSJbdI,GdJbhje GdbJUGOj(B-(3OQGSI GdLOhi GdGbJUGOjI,GdLOhi GdGbJUGOjIh GKQ GdJVNe,cjajI JUMjM dGSYGQ GdShbjI,GSYGQ GdXd dYfGUQ GdGfJGL,Jbhje GdeTQhYGJ aj Xd YOe GdJCcO (B-(3JMdjd GdLOhi GdGLJeGYjI,JMdjd GdGKGQ GdJfehjI ddeTQhY,fehPL JWHjbj ddeTQhYs
(3GdeQGLY U(B.825s
Keywords: (3GdeTGQjYs; (3OQGSI GdLOhis